Classification of costs in managerial accounting and its impact on cost management (Journal of Economic Research & Business Administration, 2016)
This article focuses on cost management through the correct classification of costs. Managerial cost accounting on the basis of cost carrier in order to enhance their credibility, more cost optimization which is why it seeks to control costs. The latter is the basis for reducing the cost of goods manufactured. Acquisition and constant increase of income characterizes the efficiency of not only the entire dairy production, but each plant individually, and within each department in the context of cost centers by type of activity. Include accounting policies the classification of costs in managerial accounting. The organization of the account of expenses on economic responsibility centers as one of the main methods of obtaining information as the main method of management accounting information support in order to control costs and the control on the kind of production, in production on the cost centers, cost center, by type of works and services, obtain based on the internal accounting.
Keywords: Management accounting; management; costs; processing of raw materials; cost classification.